Preoperative pulmonary artery pressure and mortality after lung transplantation. (June 2013) - Ohtsuka, Takashi; Flaherty, Kevin R; Lin, Jules; Lama, Vibha N; Reddy, Rishindra M; Orringer, Mark B; Chan, Kevin M; Chang, Andrew C
Background: The purpose of this study was to determine the influence of changes in pulmonary artery pressure during the waiting period on survival after lung transplantation for pulmonary fibrosis. Methods: We identified 65 patients with pulmonary fibrosis who underwent lung transplantation from 2003 to 2010. Pulmonary artery pressure determined at listing was compared with intraoperative pressure. The primary outcome was overall survival. Co-variates included type of transplantation (single or bilateral), ischemic time, recipient and donor age and sex. Results: The median age of the 65 patients undergoing transplantation was 58 years, and 27 (43%) underwent bilateral sequential transplantation. Twenty-two (35%) patients presented at transplantation with a mean pulmonary artery pressure increased by at least 10% compared to the initial pressure at the time of listing. Rising pulmonary artery pressure at transplantation was associated with increased mortality ( p  = 0.022). Other factors including type of operation, ischemic time, age, and sex, were not significantly associated with mortality. Post-transplantation survival was worse among recipients who had pulmonary artery pressure increased by at least 10% at transplantation ( p  = 0.003, logrank). Conclusions: Increasing pulmonary artery pressure while awaiting lung transplantation is associated with worse long-term survival following transplantation, and is a sign of progressively worsening disease for which greater urgency of donor organ allocation should be considered.